Perubahan Kurikulum dan Pendidikan Profesi Guru: Upaya Menemukan Arah Pendidikan yang Ideal atau Konstelasi Kekuasaan? - Apri Damai Sagita Krissandi; Kelik Agung Cahya Setiawan (SAP (Susunan Artikel Pendidikan), 2018)
The purpose of this research is to review the teacher certification program (PPG) policy as an improvement in educational quality or merely a constellation of power. The method used is a descriptive research method with documentary analysis. The PPG program, both pre-service and in-service, contains a constellation of power. It can be seen from some notes. Firstly, there is no follow-up from the PPG program. Secondly, the results of interviews by the researchers reveal that the materials provided in this program are not different from those given at the university. Thirdly, even though PPG pre-service is aimed at improving the quality of prospective teachers based on the indicators specified in the program, why do teacher training and education universities not prepare their students to be quality teachers? if they do not do so, why they do not improve the concepts and learning in lectures at their respective universities instead of adding new programs. Fourthly, there are no similar programs in countries with quality education, such as Finland, South Korea, Japan and so on. Fifthly, the tests in the admission process only administer tests that indirectly measure the cognitive level